Mentoring as a supportive pedagogy in theological training - Chiroma, Nathan H. (HTS teologiese studies, 2015)
This article contends that theological training supported by effective mentoring can contribute to the shaping of theology students in terms of their spiritual growth, character development and ministry formation. It is further argued that mentoring as a supportive pedagogy needs to be an essential element of theological education. Subsequently, guidelines for making mentoring an effective pedagogy in theological training are proposed. A lot has been written about mentoring; however this article focuses on the use of mentoring as a supportive pedagogy in denominational seminaries as a means of fostering the holistic development of theology students.